IMPLEMENTATION OF A DIFFERENCED LEARNING MODEL USING CANVA MEDIA TO INCREASE INTEREST IN LEARNING IN THE SUBJECT OF SOCIAL SCIENCES AT SMP NEGERI 1 MEJOBO.docx - Fa’izah Ainun Nufa; Annida Lailli Alayya; Nafisatur Rohmah; Dany Miftah M. Nur (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
The study aims to implement a differentiated learning model using Canva media to increase interest in learning in the subject of Social Sciences at SMP Negeri 1 Mejobo. The model aims to provide a flexible learning approach that allows students to interact with good and accurate language. The implementation of this model is crucial in ensuring that all students can effectively learn. The research includes studies on different learning methods, materials, and evaluations to make the learning experience more relevant and engaging for all students. The study also explores the impact of using Canva media as a learning tool on the effectiveness of teaching in the field of IPS. The study concludes that using Canva as a learning tool can be an effective solution for increasing interest in learning in the subject of Social Sciences at SMP Negeri 1 Mejobo. The research highlights the importance of using visual aids like Canva in enhancing the learning experience for students.